Analisis Kinerja Pegawai Camat dengan Memperhatikan Faktor Lingkungan, Budaya Kerja dan Reward (Studi pada Kantor Camat Kuala Kabupaten Bireuen) - Erizal, Erizal; Kamaruddin, Kamaruddin (Singkite Journal, 2024)
Analysis of employee performance, a necessity that continues to be evaluated, includes factors that influence it, such as the work environment, work culture and the existence of reward programs. This is the focus of this research. Using associative methods with a quantitative approach. The sample in this study was all employees of the Kuala District Office, Bireuen Regency, totaling 42 people. Data collection techniques through questionnaires and causal analysis between variables using path analysis models. As a result, it is known that (1) between the exogenous variables, namely work environment, work culture and rewards, there is a significant causal relationship, (2) so that the direct and indirect influence of each work environment, work culture and rewards factors on employee performance is 43.81 %, 33.83% and 51.03%. (3) The simultaneous contribution of the three factors to changes in employee performance levels was 54.3%.